Particle Agglomeration of Acid-Modified Tapioca Starches: Characterization and Use as Direct Compression Fillers in Tablets - Chaipat Siriwachirachai; Thaned Pongjanyakul (MDPI AG, 2022)
Acid-modified tapioca starches (AMTSs) possessed good compressibility but showed poor particle flowability for preparing tablets by the direct compression method. The aims of this work were to prepare and characterize AMTS agglomerates using polyvinylpyrrolidone (PVP) as an agglomerating agent. The dilution potential and stability studies of the AMTS agglomerates were investigated. The results showed that particle enlargement of TS and AMTS could be achieved via agglomeration using PVP. The thermal behavior and molecular interaction of the agglomerates were revealed using DSC and FTIR spectroscopy, respectively. An increase in PVP concentrations resulted in greater particle strength of the TS agglomerates and a higher acid concentration for modification enhanced the strength of the AMTS agglomerates. All agglomerates presented good particle flowability. Moreover, the AMTS agglomerates provided higher compressibility hardness than the TS agglomerates. The addition of PVP could extend the disintegration time and slow drug dissolution from the agglomerate tablets. The humidity of the storage conditions influenced the thickness and hardness of the AMTS agglomerate tablets, and good physical and chemical stability of the tablets was obtained under ambient conditions and in the refrigerator. Furthermore, the AMTS agglomerates displayed good carrying capacity and possessed desirable characteristics for use in direct compression tablets.